Discovery of novel potent human chondrosarcoma (SW1353) inhibitors: 4-(2/3/4-pyridyl)thiazole 2-acetamide derivatives - Coşkun, Göknil Pelin; Şahin, Zafer; Erdoğan, Ömer; Çevik, Özge; Biltekin, Sevde Nur; Yurttaş, Leyla; Berk, Barkın; Ülgen, Mert; Demirayak, Şeref (Elsevier B.V., 2023)
Chondrosarcoma is the most common cartilage sarcoma among adult patients. It is mainly observed after the degradation of chondrocytes in the case of cell stress. Unfortunately, the mortality among patients is high as a result of metastasis. Here in this study we have discovered some novel 4-(2/3/4-pyridyl)thiazole2-acetamide derivatives and elucidated their structure using chromatographic and spectroscopic methods. The antitumor activity profile for the synthesized compounds was performed using an MTT assay and apoptotic pathways (BAX, BCL-2) on the chondrosarcoma (SW1353) cell line. Besides, tyrosine kinase activity studies were also performed in order to understand the underlying mechanism of action. Among the synthesized compounds, there are some compounds showed excellent activity on chondrosarcoma cells. Besides, compounds showed no cytotoxicity on healthy fibroblast (L929) cell lines. Among the compounds, the compound having benzimidazole moiety showed the highest activity with IC50 value of 2.03±1.05 µM compared to doxorubicin (5.05±1.07 µM). The results indicated that the anticancer activity of the compounds might be depending on tyrosine kinase inhibiton. The compounds are also exhibited to induce apoptosis in chondrosarcoma cells. Morphological and colony observations are also successfully visualized.
Keywords: Amide; Antitumor; Apoptosis; Chondrosarcoma; Kinase; SW1357; Thiazole